Semerah padi - P. Ramlee, Tan Sri, 1928-1973 ([S.l.] : Malay Film Production [production company] ; Kuala Lumpur Sathya Production [distributor])
Bertempat di Negeri Semerah, kekalutan timbul bila Dara ditunangkan dengan Teruna sedangkan Dara dan Aduka saling mencintai.
Editor, H.R.Narayana ; fotografi, C. Ramachandran
Cast: P.Ramlee (Aduka), Nordin Ahmad (Teruna), Sa'adiah (Dara)
Keywords: Love in motion pictures; Man-woman relationships in motion pictures